Advanced persistent training : take your security awareness program to the next level - Schroeder, Jordan (California : Apress, 2017)
Gain greater compliance with corporate training by addressing the heart of the very awareness vs. compliance problem: people are human. People have incredible strengths and incredible weaknesses, and as a Information Security professional, you need to recognize and devise training strategies that take advantage of both. This concise book introduces two such strategies, which combined, can take a security awareness program to the next level of effectiveness, retention, compliance, and maturity. Security policies and procedures are often times inconvenient, technically complex, and hard to understand. Advanced Persistent Training provides numerous tips from a wide range of disciplines to handle these especially difficult situations.
Tambien disponible en formato EPUB
Keywords: SEGURIDAD EN COMPUTADORAS; TECNOLOGIA DE LA INFORMACION -- MEDIDAS DE SEGURIDAD; CAPACITACIÓN DE EMPLEADOS